The transformation to the circular economy to create new jobs- Experience of developed countries- - Benmansour, Lilia; Adjali, Dalal; Sebti, Wassila (Milev Journal of Research and Studies, 2019)
This study is concerned with solving the problem of unemployment by finding new jobs in the economies of developed countries through the transition to circular economy. The descriptive and analytical approach was adopted to give the concept of the circular economy and its possibilities to create new jobs and analyze the data of developed countries destined for the circular economy. "The circular economy includes new jobs that differ from those in the linear economy, and contribute significantly to the creation of new jobs and reduce the unemployment rates in developed countries." It was concluded that the circular economy provides many functions in (New York, London, Italy, Germany, Britain, Northern Ireland and Poland). These new positions are doubling the quest for a transition to a circular economy.